The Semiotic Meaning of One-Piece Symbols: The Inspiration of Generation Z in the August 2025 Demonstrations - Supriyadi, Iwan; Agustin, Chaerani (HK-Publishing, 2025)
Abstract Semiotics refers to an analytical discipline concerned with understanding the mechanisms through which signs function and generate meaning. This study examines Roland Barthes’ semiotic framework, which expands upon the fundamental concepts introduced by Ferdinand de Saussure, aiming to extend the application of sign analysis to broader cultural and communicative contexts. This semiotic research seeks to analyze the symbolic meanings within the anime One-Piece among Indonesia’s Generation Z, focusing on their critical stance toward governmental arbitrariness. Employing a qualitative descriptive approach and a constructivist paradigm through Roland Barthes’ semiotic analysis, this study explores symbols such as the Straw Hat, Jolly Roger, Will of D, and Grand Line. The findings reveal that these symbols are not merely fictional elements but serve as representations of solidarity, courage, and resistance against corruption, parliamentary allowance increases, mass layoffs, and unjust tax burdens. Generation Z uses One-Piece symbols as expressions of political resistance, both in public demonstrations and through digital culture, establishing a new resistance narrative that reaffirms their role as agents of socio-political change. Keywords: One Piece, Generation Z, Semiotics, Roland Barthes, Solidarity, Political Resistance